2016
DOI: 10.1186/s13052-016-0264-5
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of acute rubella infection among under-fives in Mwanza: a threat to increasing rates of congenital rubella syndrome in Tanzania

Abstract: BackgroundControl of rubella infection is essential for preventing congenital rubella syndrome (CRS) and one of the important steps is to define a target population for vaccination. Therefore this study was done to determine serological evidence of acute rubella infection among under-fives in order to anticipate the magnitude of rubella virus transmission in Tanzania.MethodsA cross-sectional study involving children aged between 1 and 59 months was conducted between September and October 2014 before national r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…The seroprevalence of CMV (89.66%) presented in this study is similar to a study done by Neirukh et al in Palestine which is 88% and Nahla et al in Sudan showd 94.3% seropositivity 11,7 . In this study IgM/IgG seropositivity against Rubella was 86.21%, is similar to a study done by Nazme 14,10 . Nazme et al from Dhaka Shishu hospital reported 28% children were seropositive for rubella IgM among suspected congenital rubella syndrome cases 6 .…”
Section: Resultssupporting
confidence: 91%
“…The seroprevalence of CMV (89.66%) presented in this study is similar to a study done by Neirukh et al in Palestine which is 88% and Nahla et al in Sudan showd 94.3% seropositivity 11,7 . In this study IgM/IgG seropositivity against Rubella was 86.21%, is similar to a study done by Nazme 14,10 . Nazme et al from Dhaka Shishu hospital reported 28% children were seropositive for rubella IgM among suspected congenital rubella syndrome cases 6 .…”
Section: Resultssupporting
confidence: 91%
“…Age group, sex, and province were associated with rubella susceptibility in unadjusted analyses but only province of residence and age group remained associated with rubella susceptibility in multivariable analysis. Several studies in Sub-Saharan Africa have described the predominance of rubella infections in children [22][23][24][25] and a recent analysis of rash-based surveillance data in South Africa revealed similar results. 26 Rubella infections occurring in childhood result in most individuals being immune by the time they are adolescents or adults.…”
Section: Discussionmentioning
confidence: 64%
“…[10][11][12][13]27 This could be due to the nature of contacts between younger individuals that favor transmission of infections such as rubella when compared to contacts between older individuals. 28 Increased susceptibility to rubella among younger individuals coupled with evidence of increased rubella incidence in this age group [22][23][24]26 justifies targeting children below 15 y old 29 for mass vaccination during RCV introduction rather than just infants in routine immunization activities. Following rubella vaccine introduction into the routine EPI schedule, the average age of infection is likely to increase and a similar study will be required in future to assess population immunity and adapt vaccination strategies to minimize the risk of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to screen for other causes of congenital anomalies during the diagnosis of potential ZIKV cases, particularly in developing countries where these infections are most prevalent. [27][28][29][30][31][32][33][34][35][36] The majority of the articles in this review included well-studied cases highlighting the widely varying patterns of congenital ZIKV presentation. As has been done for the 37 there is a need to establish a pathognomonic features list and case definitions for congenital ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%